Name that Percussive Tune: Associative Memory and Amplitude Envelope†. Issue 7 (July 2017) - Schutz, Michael; Stefanucci, Jeanine K.; Sarah, H. Baum; Roth, Amber
A series of experiments demonstrated novel effects of amplitude envelope on associative memory, with tones exhibiting naturally decaying amplitude envelopes (e.g., those made by two wine glasses clinking) better associated with target objects than amplitude-invariant tones. In Experiment 1 participants learned associations between household objects and 4-note tone sequences constructed of spectrally matched pure tones with either "flat" or "percussive" amplitude envelopes. Those hearing percussive tones correctly recalled significantly more sequence–object associations. Experiment 2 demonstrated that participants hearing percussive tones learned the associations more quickly. Experiment 3 used "reverse percussive" tones (percussive tones played backwards) to test whether differences in overall energy might account for this effect, finding they did not lead to the same level of performance as percussive tones. Experiment 4 varied the envelope at encoding and retrieval to determine which stage of the task was most affected by the envelope manipulation. Participants hearing percussive tones at both encoding and retrieval performed significantly better than the other three groups (i.e., flat at encoding/percussive at retrieval, etc.). We conclude that amplitude envelope plays an important role in learning and memory, a finding with relevance to psychological research on audition and associative memory, as well as practical relevance for improving human–computer interface design.